Improved quality of life following direct‐acting antiviral treatment for chronic hepatitis C infection in Rwanda: Results from a clinical trial in sub‐Saharan Africa (the SHARED study). Issue 1 (4th October 2020) - Van Nuil, Jennifer Ilo; Umutesi, Grace; Shumbusho, Fabienne; Kateera, Frederick; Dushimimana, Jean de Dieu; Muvunyi, Claude Mambo; Musabeyezu, Emmanuel; Mukabatsinda, Constance; Ntirenganya, Cyprien; Kabahizi, Jules; Serumondo, Janvier; Makuza, Jean Damascene; et al.
Abstract: Around 71 million people are living with chronic hepatitis C virus (HCV) infection, with approximately 14% residing in sub‐Saharan Africa. Direct‐acting antiviral (DAA) therapies offer clear benefits for liver‐related morbidity and mortality, and data from high‐income settings suggest that DAA treatments also provide significant benefits in terms of health‐related quality of life (HRQL). In this study, we assessed the effect of DAA treatment on HRQL for individuals treated for HCV in a clinical trial in Rwanda. We assessed the HRQL of participants using an 83‐question composite survey at Day 0 ('baseline') and Week 24 ('endpoint'). Data were analysed in R. A total of 296 participants were included in this analysis. Their ages ranged from 19 to 90, and 184 (62.2%) were female. There were significant improvements from baseline to endpoint median scores for all physical and mental quality of life sub‐scales. Additionally, a reduction—before and after treatment—in the proportion of those classified as depressed and needing social support was statistically significant (both P < .001). Economic productivity increased after treatment ( P < .001), and households classified as food secure increased from baseline to endpoint ( P < .001). These results demonstrate that Rwandans with chronic HCV infection experience both clinical and HRQL benefits, including household‐level benefits like substantial gains in workforce stability, economic productivity, and poverty alleviation, from DAA treatment. A stronger demonstration of accurate and broader household‐level benefits achieved through treatment of HCV with DAAs will help financing and investment for HCV in resource‐constrained settings become an urgent priority.